Mapping Stellar Population of Seyfert 2: The AGN influence - Marinho, Lais; Riffel, Rogério (Cadernos de Astronomia, 2026)
We investigate the circumnuclear stellar populations of 12 Seyfert 2 galaxies selected from the Swift-BAT AGN Spectroscopic Survey based on their ultra-hard X-ray luminosity (14–195 keV). Using MUSE/VLT integral field spectroscopy and spectral synthesis, we spatially characterize the stellar populations in the central regions of the galaxies. Preliminary results indicate signatures of central stellar rejuvenation, with significant contributions from young and intermediate-age populations and the presence of radial metallicity gradients. Moderate correlations between stellar properties and AGN activity indicators suggest that both gas recycled by evolved stars and gas associated with recent star formation may contribute to supermassive black hole fueling. Given the exploratory nature of the sample, these results should be regarded as preliminary.